2016
DOI: 10.5194/isprsarchives-xli-b5-895-2016
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy Assessment of a Uav-Based Landslide Monitoring System

Abstract: ABSTRACT:Landslides are hazardous events with often disastrous consequences. Monitoring landslides with observations of high spatio-temporal resolution can help mitigate such hazards. Mini unmanned aerial vehicles (UAVs) complemented by structure-from-motion (SfM) photogrammetry and modern per-pixel image matching algorithms can deliver a time-series of landslide elevation models in an automated and inexpensive way. This research investigates the potential of a mini UAV, equipped with a Panasonic Lumix DMC-LX5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 21 publications
2
37
0
Order By: Relevance
“…James and Robson [38] highlighted how unresolved elements of the camera model (lens distortion) can propagate as errors in UAS-DEMs (derived digital elevation models), and how this can be addressed by incorporating oblique images. Other studies have highlighted the importance of flight line configurations [39], as well as minimizing image blur [34]. There is a need to consolidate this evidence to develop best practice guidance for optimizing UAS SfM (structure-from-motion) measurement quality, whilst maintaining ease of use and accessibility.…”
Section: Preflight Planningmentioning
confidence: 99%
See 1 more Smart Citation
“…James and Robson [38] highlighted how unresolved elements of the camera model (lens distortion) can propagate as errors in UAS-DEMs (derived digital elevation models), and how this can be addressed by incorporating oblique images. Other studies have highlighted the importance of flight line configurations [39], as well as minimizing image blur [34]. There is a need to consolidate this evidence to develop best practice guidance for optimizing UAS SfM (structure-from-motion) measurement quality, whilst maintaining ease of use and accessibility.…”
Section: Preflight Planningmentioning
confidence: 99%
“…This task is often referred to as registration, and is conventionally dependent on establishing ground control points (GCPs) which are fixed by a higher-order control method (usually Global Navigation Satellite System-GNSS or Global Positioning System). A number of studies have examined the effect of GCP networks (number and distribution) in UAS surveys, showing that significant errors are expected in SfM-based products where GCPs are not adopted [39,40]. Nevertheless, systematic DEM error can Remote Sens.…”
Section: Preflight Planningmentioning
confidence: 99%
“…The general steps and specific settings of processing were as follows: after creating a sparse dense cloud, a dense point cloud was generated using medium quality mode and so-called aggressive depth filtering. The latter means that minor surface details are filtered out [31]. According to [8], the reduced quality mode during dense point cloud generation does not considerably affect the DEM accuracy but leads to a reduced processing time.…”
Section: Data Processingmentioning
confidence: 99%
“…According to [8], the reduced quality mode during dense point cloud generation does not considerably affect the DEM accuracy but leads to a reduced processing time. References [8,31] showed that aggressive filtering reduces minor surface details. In our case we do not focus on single surface spots and thus a smoothed DEM is acceptable.…”
Section: Data Processingmentioning
confidence: 99%
“…The latter facilitates autonomous UAV flights using pre-programmed flight plan parameters. Peppa et al (2016) provides further details and specifications of the UAV.…”
Section: Uav Surveymentioning
confidence: 99%